A New Data Mining and Visualization Tool for Brazilian Educational Indicators - Pinho, Rodrigo Silveira de; Silva, Danilo Borges da; Oliveira, Suzana Matos França de (Anais do Encontro Unificado de Computação do Piauí (ENUCOMPI); 2021: Anais do XIV Encontro Unificado de Computação do Piauí e XI Simpósio de Sistemas de Informação, 2021)
The National Institute of Educational Studies and Research Anísio Teixeira provides open data that help to understand Brazilian Education through Educational Indicators. Despite the easy access to the data, it is hard to manipulate and analyze it to understand the educational scenario in different contexts. This work presents a new visualization tool, inspired by the data mining process, which aims to allow the extraction of knowledge through these indicators using selections provided by users in a very simple manner. To show the tool's potential, graphics of several works were recreated and new graphics are presented.